Imperial Muslims : Islam, Community and Authority in the Indian Ocean, 1839-1937 - Reese, Scott Steven; Project Muse. (Edinburgh : Edinburgh University Press, 2018)
A transregional history of Muslim community in the British Empire. The webs, nodes and networks created by Britain's Indian Ocean Empire during the nineteenth and twentieth centuries are here explored in the context of their personal and social impact. Using the British Settlement of Aden as its focus, the book examines the development of a local community within the spaces created by imperial rule. It explores how individuals from widely disparate backgrounds brought together by the networks of empire created a cohesive community utilizing the one commonality at their disposal: their faith. Specifically, it examines how religious institutions and spiritual ideas served as parameters for the creation of community and the kinds of symbolic and cultural capital an individual needed to attain communal membership and influence within the confines of imperial rule. Key Features. Explores the social consequences of Britain's creation of an Indian Ocean empire that brought millions of Muslim subjects under a single political umbrella for the first time in the modern era The case of Aden allows an examination of a community that was created by the colonial moment, rather than just shaped by it Shows how individuals drawn together from enormously diverse geographic, cultural and social backgrounds manage the realities of everyday life together via a common Islamic discursive tradition Provides insight into how believers accessed an Islamic ontology and shared concepts of the universe, along with more observable institutions to shape their community within the confines of imperial rule
Introduction : a community of Muslims -- Hanuman's tunnel : collapsing the space between Hind and Arabia in the Arab imaginary -- Aden, the Company and Indian Ocean interests -- Claims to community : mosques, cemeteries and the universe -- "The Qadi is not a judge" : the Qadi's courts, community and authority -- "An innocent amusement" : marginality, spirit possession and the moral community -- Scripturalism, Sufism and the limits of defining public religiosity.
Description based on print version record.
Keywords: Social change; Religious communities; Muslims; British colonies; RELIGION -- Islam -- General; Communautes (Religion) -- Indien, Region de l'ocean -- Histoire -- 19e siecle; Musulmans -- Indien, Region de l'ocean -- Histoire -- 19e siecle; Social change -- Indian Ocean Region -- History -- 20th century; Religious communities -- Indian Ocean Region -- History -- 19th century; Muslims -- Indian Ocean Region -- History -- 19th century; Indian Ocean Region; Grande-Bretagne -- Colonies; Great Britain -- Colonies; History; Electronic books